ANALISIS KESULITAN BELAJAR MATEMATIKA DI MASA PANDEMI COVID-19 SISWA KELAS IV SD NEGERI 2 BUMIREJO - Dwi Rezeki, Yuvita; Trisniawati, Trisniawati; Titi Muanifah, Mahmudah (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to describe how the type of mathematics learning difficulties experienced by students, factors that cause difficulty learning mathematics, and efforts to overcome mathematical learning difficulties. The focus of the problems discussed in this study is the cause of the difficulty of learning mathematics in the time of the Covid-19 students of the fourth-grade students of Bumirejo. This research is descriptive qualitative research. This research was conducted at the SD Negeri 2 Bumirejo with the subject of class IV teachers, parents of fourth-grade students, and fourth-grade students of SD Negeri 2 Bumirejo. The techniques used to collect data are observation, interviews, documentation, and learning test results. Data analysis was carried out with data reduction, data presentation, and conclusion withdrawal. The results showed that 1) the most difficulties carried out by students, namely in the difficulty of solving the problem of stories with a percentage of 88.46%, difficulties in planting the concept of mathematics 69.23%, difficulties in calculating the division of 34.61%. 2) Factors that cause student learning difficulties include negative attitudes in learning mathematics, lack of interest in students in learning mathematics, students prefer to play with peers than doing assignments, and students easier to understand the material when learning to face face to learn from home. 3) Efforts made to overcome learning difficulties carried out by teachers, students, and parents. The effort made by the teacher is to provide direction to parents and help students when difficult. Efforts made by students, namely by participating in lessons, and efforts made by parents, namely by motivation and accompanying students to learn.